2020
DOI: 10.1186/s13024-020-00415-2
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic phenotype in mouse and humans reduces the number of microglia around β-amyloid plaques

Abstract: Background Alzheimer’s disease (AD) is the most common neurodegenerative disease and type 2 diabetes (T2D) plays an important role in conferring the risk for AD. Although AD and T2D share common features, the common molecular mechanisms underlying these two diseases remain elusive. Methods Mice with different AD- and/or tauopathy-linked genetic backgrounds (APPswe/PS1dE9, Tau P301L and APPswe/PS1dE9/Tau P301L) were fed for 6 months w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 123 publications
0
15
0
Order By: Relevance
“…Likewise, the close relationship between AD and T2D has been long analyzed ( Biessels and Despa, 2018 ; Vieira et al, 2018 ). Studies on animal models have shown that metabolic alterations may affect different amyloid species and amyloid deposition, although the effects seem to be highly dependent on the specific animal model used ( Ramos-Rodriguez et al, 2014 ; Wang et al, 2014 ; Chatterjee and Mudher, 2018 ; Natunen et al, 2020 ). On the other hand, while it is widely accepted that cognitive dysfunction is an important and common comorbidity of diabetes, this effect does not seem to be directly related to alterations in amyloid pathology, and previous studies have reported no differences in cerebrospinal fluid amyloid-β (Aβ)-42 levels, global or regional AD pathology, or amyloid burden ( Arvanitakis et al, 2006 ; Moran et al, 2015 ; Pruzin et al, 2017 ; Biessels and Despa, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the close relationship between AD and T2D has been long analyzed ( Biessels and Despa, 2018 ; Vieira et al, 2018 ). Studies on animal models have shown that metabolic alterations may affect different amyloid species and amyloid deposition, although the effects seem to be highly dependent on the specific animal model used ( Ramos-Rodriguez et al, 2014 ; Wang et al, 2014 ; Chatterjee and Mudher, 2018 ; Natunen et al, 2020 ). On the other hand, while it is widely accepted that cognitive dysfunction is an important and common comorbidity of diabetes, this effect does not seem to be directly related to alterations in amyloid pathology, and previous studies have reported no differences in cerebrospinal fluid amyloid-β (Aβ)-42 levels, global or regional AD pathology, or amyloid burden ( Arvanitakis et al, 2006 ; Moran et al, 2015 ; Pruzin et al, 2017 ; Biessels and Despa, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, although the pathological significance of serum sTREM2 levels in the continuum of cognitive impairment in type 2 diabetes remains unclear, an in vitro study showed that high levels of glucose activated microglia to up-regulate TREM2 expression and induce an inflammatory response ( 36 ). Furthermore, another study reported that diabetic conditions impaired microglial function in both mice and humans ( 18 ). Hence, as a possibility that serum sTREM2 are derived from adipose tissue ( 19 ) and activated microglia ( 15 ) exists, we speculate that hyperglycemia and/or insulin resistance first triggers the elevation of sTREM2, even in a cognitively normal stage in diabetic conditions, ultimately leading to microglial dysfunction and cognitive impairment if diabetic conditions are not improved.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the roles of TREM2 in glucose metabolism remain controversial. Conversely, type 2 diabetes-related metabolic dysfunction altered microglial TREM2 signaling and resulted in microglial dysfunction, which in turn led to cognitive impairment ( 18 ), thereby suggesting pathological implications of TREM2 in the development of diabetes-related cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Another study created a mouse model with both AD-linked genetic backgrounds and the diabetic phenotype. These mice demonstrated impaired microglial responses to AD pathologies, with fewer microglia around Aβ-amyloid plaques and increased number of dystrophic neurites These repressive responses were found to be linked to TREM2-related processes [36]. In addition to these studies in mice, a recent longitudinal study of the DIAN cohort found that faster longitudinal increase in CSF sTREM2 correlated with slower amyloid deposition, slower cortical thinning in the precuneus, and slower decline in cognitive functions in presymptomatic AD-linked mutation carriers [23].…”
Section: Discussionmentioning
confidence: 99%